2013
DOI: 10.1111/jasp.12133
|View full text |Cite
|
Sign up to set email alerts
|

Gamers just want to have fun? Toward an understanding of the online game acceptance

Abstract: This study sought to examine the factors affecting the acceptance of an entertainment medium, particularly online games, by expanding the technology acceptance model. To measure factors affecting the acceptance of online games, we fielded a survey with 244 gamers serving as respondents. Perceived usefulness, enjoyment, and economic value were found to have a positive influence on attitude toward gaming, whereas perceived ease of use was not a significant predictor. In addition, we found that gender and game ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 46 publications
1
21
0
1
Order By: Relevance
“…Moreover, characteristics of the app might have been less suitable for males, thus leading to reduced effects. For example, males may have a preference for games involving competition and show greater motivation to play in a social context compared to their female counterparts (Lucas & Sherry, 2004; Veltri et al, 2014; Yoon et al, 2013). The gamified app used in the present study had few competitive aspects and was not explicitly social.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, characteristics of the app might have been less suitable for males, thus leading to reduced effects. For example, males may have a preference for games involving competition and show greater motivation to play in a social context compared to their female counterparts (Lucas & Sherry, 2004; Veltri et al, 2014; Yoon et al, 2013). The gamified app used in the present study had few competitive aspects and was not explicitly social.…”
Section: Discussionmentioning
confidence: 99%
“…Such differences may be particularly important to consider in the context of gamified mental health interventions (Veltri, Krasnova, Baumann, & Kalayamthanam, 2014). Overall, studies have shown that females play games less frequently, have less of a preference for games involving competition and a show a reduced motivation to play in a social context compared to male counterparts (Lucas & Sherry, 2004; Veltri et al, 2014; Yoon, Duff, & Ryu, 2013). Although gender difference in attention biases are poorly understood (Bar-Haim et al, 2007; Sass et al, 2010), one study showed that females with elevated mood symptoms, such as anxiety and depression, are more likely to show biased processing of threat and other negative information and less reduction of biases via training (Beshai, Prentice, Dobson, & Nicpon, 2014).…”
mentioning
confidence: 99%
“…Yoon et al () used the technology acceptance model and found that enjoyment, usefulness, and economic value impact gamers' attitude to online games. While the study of Yoon et al () emphasized the economic value of online gaming, this study highlights the social value of online gaming. Specifically, gamers enjoy social activities with real people within computer‐mediated environments to experience sense of community and build social capital.…”
Section: Discussionmentioning
confidence: 99%
“…Social networks in various online media have been widely investigated. Among them, online games have been a recent focus in both the literature on communication (e.g., Taylor, Jenson, de Castell, & Dilouya, ; Yoon, Duff, & Ryu, ) and electronic commerce (e.g., Hsiao & Chiou, ; Wu & Liu, ). Focal issues include why gamers continue to play online games, and social aspects have been verified as providing critical impetus.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the reasons and motivations as to why people use them can also be expected to vary. Thus far however, games have commonly been seen as a singular type of technology: "Gamers just want to have fun" (Wu & Li 2007;Yoon et al 2013).…”
Section: Introductionmentioning
confidence: 99%